(untitled) (Journal of Asian Development Studies, 2013)
Human-made disasters have a different impact on adults and children where young children are most vulnerable to the negative effects of disaster owing to their lack of awareness of preventive measures and inability to cope with post-disaster stress and recovery process. This study was aimed at exploring the psychological and behavioral impact of disaster on children and the role of caregivers in the children’s rehabilitation in orphanages. The sample size consisted of 18 children (9 boys and 9 girls) and 9 primary caregivers (mother-maids) taken via purposive convenience sampling from Pakistan Bait-ul-Mal’s Sweet Homes Orphanages. A semi-structured interview in Urdu was conducted to obtain desired data. The results showed that disasters have a negative effect on the psycho-social state of the children in terms of increased dependency, sleep disturbances/bad dreams, sadness/emotion regulation, social withdrawal and need for social support from elders and peers. The traditional gender role socialization contributes to the risk of problems after disaster. There were gender differences in expression of emotions where girls were more expressive than boys about their traumatic experience. The girls preferred to share feelings with their peers whereas the boys were more comfortable sharing with the mother-maids than with the other children. Both the girls and boys were non-cooperative initially but the boys also showed aggressive attitude. According to the caregivers’ reports, over time, the children showed an improvement in their emotional and behavioral disturbances. Thus it seems likely that the smooth rehabilitation process and healthy social relations with peers and caregivers may minimize the negative effects of disaster. It is suggested that psycho-social therapeutic interventions like catharsis, play and art therapy are needed which help the children cope with the effects of disaster. Training of caregivers can help to screen out children who need professional medical help.